Optimization of palm oil biodiesel production: Environmental impact analysis and POME waste utilization - Paminto, Ari Kabul; Karuniasa, Mahawan; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Indonesia is still an energy importer, especially in the form of crude oil and fuel products to meet the needs of its industrial sector. The reduced production of fossil energy, especially oil, as well as the global commitment to reducing greenhouse gas emissions, has prompted the Indonesian government to continue to support the role of new and renewable energy. The production of palm oil-based biodiesel is faced with a number of environmental problems, which may occur from the release of emissions during the production of FFB (Fresh Fruit Bunches), CPO (Crude Palm Oil), and biodiesel. Therefore, the purpose of this research is to compile an LCI (Life Cycle Inventory) covering the production of FFB, CPO, and biodiesel; analyze the environmental impact of the CPO bodysel production process which includes CO2 (eq) emissions, acidification and eutrophication; and develop a life cycle concept for biodiesel production from palm oil as a renewable energy. Methods: The method used in this study is a combination of quantitative LCA (Life Cycle Assessment) and AHP (Analytical Hierarchy Process) and qualitative. Findings: The results of this study are LCI in 1 ton of biodiesel consisting of NPK fertilizer of 141.1 Kg; herbicide (0.25 Kg); water (1578 m3), diesel oil (25 Kg); fresh fruit bunches of 5.67 tons; electricity of 33.8 kWh, POME (Palm Oil Mill Effluent) (3,47 m3), CPO needed for biodiesel conversion of 1.17 tons; methanol (0.41 tons), and 0.01 tons of Sodium Hydroxide. The total CO2 emission (eq) of biodiesel production from palm oil is 1489 Kg CO2 (eq), eutrophication is 1.12 Kg PO43- (eq) and acidification is 3.06 Kg SO2 (eq). With the largest contribution of CO2 (eq) emissions in CPO production and the contribution of eutrophication and acidification in oil palm plantations or FFB production (Fresh Fruit Bunches). Environmental hotspot of LCA, CO2 (eq) emissions from palm oil biodiesel production show that 53% mainly comes from POME (Palm Oil Mill Effluent) waste, other contributors are NPK fertilizers (23%), methanol (18%), and diesel oil (7%). Hotspot eutrophication showed that 61% mainly came from NPK fertilizer, methanol (20%), diesel oil (11%), and POME waste (8%). Hotspot acidification showed that 48% mainly came from NPK fertilizers, methanol (28%), POME waste (13%), and diesel oil (11%). Conclusion: The concept of a biodiesel production life cycle can be applied with the best alternative utilization of POME waste with a priority weighting of 0.357 and a CO2(eq) emission criterion of 0.494. From the optimization of the life cycle of biodiesel production with the use of POME, the potential for emission reduction is 667.2 Kg CO2 (eq). Novelty/Originality of this Study: This study's novel application of LCA evaluates the environmental impacts of biodiesel production from palm oil in Indonesia, identifying critical hotspots in CO2 emissions, eutrophication, and acidification. Additionally, it proposes an innovative optimization approach by utilizing POME to significantly reduce greenhouse gas emissions, highlighting a viable path for enhancing the sustainability of biodiesel production.